2011
DOI: 10.1271/bbb.100454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Superoxide Anion Radicals Generated from an Aqueous Extract of Particulate Phase Cigarette Smoke by Electron Spin Resonance Using 5,5-Dimethyl-1-pyrroline-N-oxide

Abstract: The reactive oxygen species generated by an aqueous extract of the particulate phase of cigarette smoke were evaluated by an electron spin resonance (ESR) analysis, using spin-trapping agents, and by comparing with model reaction systems. The ESR signals of DMPO-OH were detected from the extract by using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO). These signals were eliminated by adding superoxide dismutase, but hardly by catalase. These responses of the ESR signals to the scavengers were similar to those of a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In fact, extracts of cigarette smoke contain various ROS, such as hydrogen peroxide [25], superoxide [9, 26], hydroxyl radicals [9], peroxy radicals [9], and nitric oxide [9]. In addition, numerous papers have reported that cigarette smoke induces not only ROS production, antioxidant depletion, neutrophil infiltration, and inflammation in lung [23], but also increased levels of oxidative stress markers, such as inflammatory cytokines, in the bloodstream [6].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, extracts of cigarette smoke contain various ROS, such as hydrogen peroxide [25], superoxide [9, 26], hydroxyl radicals [9], peroxy radicals [9], and nitric oxide [9]. In addition, numerous papers have reported that cigarette smoke induces not only ROS production, antioxidant depletion, neutrophil infiltration, and inflammation in lung [23], but also increased levels of oxidative stress markers, such as inflammatory cytokines, in the bloodstream [6].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction of xanthine with XOD produces both superoxide and hydrogen peroxide directly (Takanami and Nakayama 2011). In addition, XOD contains transition metals required for catalysis, namely molybdenum and iron which play a key role during the catalytic activity of XOD.…”
mentioning
confidence: 99%
“…However, such superoxide generation is transient due to the high reaction rate constant of semiquinones' interactions with oxygen in the air [10], and semiquinones are not guaranteed to produce superoxide in aqueous media with a low oxygen concentration [11]. Thus, additional sources and mechanisms seem to be involved in CS-induced superoxide formation in aqueous media [12].…”
Section: Introductionmentioning
confidence: 99%